SINERGISITAS SISTEM AGURON-GURON DAN PENDIDIKAN KEKINIAN BAGI SULINGGIH DAN CALON SULINGGIH MENUJU MILENIUM BARU - Ambarnuari, Mery; Anak Agung Ayu Alit Widyawati (Sphatika: Jurnal Teologi, 2026)
Hindu religious education plays a strategic role in preserving the spiritual, moral, and cultural values of the Hindu community amid the dynamics of globalization and modernization. One traditional educational system that plays a significant role in shaping Hindu religious leaders is the aguron-guron system, a parampara-based educational model that emphasizes a deep spiritual and ethical relationship between the teacher (nabe) and the disciple (nanak). However, contemporary developments demand adaptation and synergy between the aguron-guron system and formal as well as non-formal education systems in order to remain relevant and effective. This study aims to examine the traditional aguron-guron education system, the formal and non-formal education systems for sulinggih and prospective sulinggih, and the forms of synergy among these systems in responding to the challenges of the new millennium. The research employs a qualitative method with a literature review approach, drawing upon Hindu religious texts, educational literature, and scholarly studies related to priesthood education. The findings indicate that the aguron-guron system plays a crucial role in shaping the spiritual and moral character of prospective sulinggih, while formal education provides an academic foundation and critical thinking skills, and non-formal education strengthens practical competencies in the performance of religious rituals. The synergy among these three educational systems results in an ideal educational model capable of producing sulinggih who possess spiritual depth, broad scholarly insight, and contextual abilities to address the challenges faced by the Hindu community in contemporary society. Therefore, the integration of the aguron-guron system with formal and non-formal education is a strategic necessity for the sustainable development of Hindu religious education.